Ethanol Production, Food and Forests - Saraly Andrade de Sa; Charles Palmer; Stefanie Engel (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This paper investigates the direct and indirect impacts of ethanol production on land use, deforestation and food production. A partial equilibrium model of a national economy with two sectors and two regions, one of which includes a residual forest, is developed. It analyses how an exogenous increase in the ethanol price affects input allocation (land and labor) between sectors (energy crop and food). Three potential effects are identified. First, the standard and well-documented effect of direct land competition between rival uses increases deforestation and decreases food production. Second, an indirect displacement of food production across regions, provoked by a shift in the price of food, increases deforestation and reduces the total output of the food sector. Finally, labor mobility between sectors and regions tends to decrease food production but also deforestation. The overall impact of ethanol production on forest conversion is ambiguous, providing a number of interesting pointers to further, empirical research.
Keywords: Q11; Q24; Q42; 330; Ethanol; Deforestation; Indirect impacts; Land use; Migration